Interacting Science through Web Quests - Unal, Ahmet; Karakuş, Melek Altıparmak (Horizon Research Publishing Co., Ltd., 2016)
The purpose of this paper is to examine the effects of WebQuests on elementary students' science achievement, attitude towards science and attitude towards web supported education in teaching 7th grade subjects (Ecosystems, Solar System). With regard to this research, "Science Achievement Test", "Attitude towards Science Scale" and "Attitude towards Web Supported Education Scale" have been applied to seventh grade elementary science students as pre-test and post-test. Moreover, while the experimental group was using WebQuest activities during the lesson, the control group students used concurrent Science and Technology curriculum based activities. The findings of the research have examined and analyzed through the SPSS program. The outputs showed that there emerged a meaningful difference between the control and experimental group favoring the experimental group for science achievement and attitude towards web supported education whereas no meaningful difference between control and experimental group for attitude towards science has been found.
Keywords: 4. Education